2008
DOI: 10.1002/j.2048-7940.2008.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Bedside Dysphagia Screening: A Comparison of Registered Nurses and Speech Therapists

Abstract: Evidence‐based guidelines suggest that stroke patients should be screened for dysphagia before oral intake. The purpose of this study was to validate a dysphagia screening tool comparing registered nurses (RNs) with speech therapists (STs). All stroke unit patients who received predetermined scores on specific items of the National Institutes of Health Stroke Scale were eligible for screening. The trial consisted of three parts (with swallow, cough, and vocal quality observed during each part): 1 teaspoon lemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…In these studies, the patient had to ingest the liquid and some signs were observed during and after the intake. There were also articles that showed screening instruments with two procedures (17,22,28,39) , containing one observational part and the other a swallowing test using water or food of different viscosities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the patient had to ingest the liquid and some signs were observed during and after the intake. There were also articles that showed screening instruments with two procedures (17,22,28,39) , containing one observational part and the other a swallowing test using water or food of different viscosities.…”
Section: Resultsmentioning
confidence: 99%
“…Schrock et al (29) ; Weinhardt et al (39) Multiple sclerosis Bergamaschi et al (23) Duchenne muscular dystrophy Hanayama et al (25) Inclusion body myositis Cox et al (31) Head and neck cancer Govender et al (35) ; Dwivedi et al (37) Parkinson's disease Manor et al (33) Heterogeneous etiologies (neurological disorders, head and neck cancer, esophageal abnormalities, respiratory and heart problems, among others)…”
Section: Underlying Pathologies Articlesmentioning
confidence: 99%
“…Studies have shown that other healthcare providers can safely perform the initial screening before the speech language pathologist assessment. 903,915,916 In a prospective 15-hospital study, use of a formal dysphagia screening protocol, which incorporated an evidence-based screening tool, was associated with improved compliance with dysphagia screenings and a significantly reduced risk of pneumonia. 917 The Toronto Bedside Swallowing Screening test, an evidence-based tool for swallow assessment, has been evaluated successfully for interrater reliability and predictive validity.…”
Section: Nutrition and Hydrationmentioning
confidence: 99%
“…[6][7][8] Of these cases, 65% present this symptom within the first 5 days of hospitalization, leading to a sixfold increase in risk for aspiration pneumonia and a threefold increase for mortality. [9][10][11][12] Pneumonia after stroke is frequently associated with the presence of laryngotracheal aspiration, 2%-25% of which are concomitant with silent aspirations. 13,14 Diverse protocols have suggested that the National Institutes of Health Stroke Scale (NIHSS) can be a predictor in the identification of dysphagia risk in patients after stroke, despite not making reference to deglutition.…”
Section: Introductionmentioning
confidence: 99%